DYNAMICS OF THE PRO-INFLAMMATORY CYTOKINES CONCENTRATION INDICES IN THE BLOOD SERUM OF PATIENTS WITH RECURRENT DEPRESSIVE DISORDER - Kozhyna, G.M.; Tereshina, I.F.; Zelenska, K.O.; Ogorenko, V.V.; Venger, O.P. (World of Medicine and Biology, 2019)
In patients with recurrent depressive disorder, RDR (33.1) a significant growth of the pro-inflammatory cytokines (IL-1β, TNFα) concentration was observed in the blood serum. Inclusion of the modern combined plant origin adaptogen into the treatment complex for patients with recurrent depressive disorder (RDD) (33.1) in the pathogenic aspect contributes to the positive dynamics of the pro-inflammatory cytokines (IL-1β, TNFα) concentration in the blood serum of the examined patients. In view of this, the purpose of this adaptogen can be considered pathogenetically substantiated and clinically promising in the treatment of patients with recurrent depressive disorder (RDD) (33.1).
Keywords: recurrent depressive disorder; pro-inflammatory cytokines (IL-1β; TNFα); adaptogen; outpatient treatment